2018
DOI: 10.5301/tj.5000634
|View full text |Cite
|
Sign up to set email alerts
|

C677T and A1298C polymorphisms of methylene tetrahydrofolate reductase in non-Hodgkin lymphoma: southeast Iran

Abstract: Combination of CT and TT genotypes of C677T polymorphism conferred a significantly higher risk for NHL. It is recommended to investigate further the potential role of this polymorphism in NHL development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…33 In our series, this combination was present in patients having non-Hodgkin lymphoma and this finding would deserve to be further investigated. 34…”
Section: Discussionmentioning
confidence: 99%
“…33 In our series, this combination was present in patients having non-Hodgkin lymphoma and this finding would deserve to be further investigated. 34…”
Section: Discussionmentioning
confidence: 99%
“…Faganel et al confirmed that MTX clearance decreased to 73.8% in in childhood ALL and malignant lymphoma with the (29). Therefore, patients carrying variant alleles might have an increased risk of developing higher intolerance to MTX (14). The elimination of MTX mainly relies on kidney and liver.…”
Section: Mthfr C677tmentioning
confidence: 99%
“…The negative effects of polymorphism C677T might be explained by the decreased MTHFR activity. In the case of C677T, C nucleotide is substituted by T nucleotide at position 677, resulting in an amino acid exchange from alanine to valine in the respective amino acid sequence, which lowers the affinity of the enzyme for its cofactor, flavin adenine dinucleotide (5,14). As a result, individuals in mutant status (C677T and T677T) exhibit 60 and 30% of the normal MTHFR activity, respectively (4,5).…”
Section: Mthfr C677tmentioning
confidence: 99%
See 2 more Smart Citations